Organizational designs for managing incremental and radical innovation - Brynjar Freyr Halldórsson 1989- (2013)
This paper explores what types of organizational design mature firms in Iceland employ to host incremental and radical innovation. As innovation is generally recognized to be important for a firm’s competitive success, companies need to find the right balance between exploitation through incremental innovation and exploration through radical innovation. This paper draws on a case study by Tushman, Smith, Wood, Westerman, & O'Reilly (2004), which describes four different approaches of organizational design that organizations can employ in managing radical and incremental innovation: functional design, cross-functional teams, ambidextrous design and unsupported teams. A sample of six business units in Iceland, active in innovation and competing in a variety of industries, was explored for this research. Senior managers that were highly involved in innovation projects at their respective companies were interviewed. Each organization was mapped, based on whether it had high or low senior management integration, and high or low structural differentiation. Of the companies explored, three were found to employ a functional design, two cross-functional teams, and one employs an ambidextrous design. Despite efforts to find a case company that might employ unsupported teams, none of the case firms were found to employ that particular organizational design.